Cohort profile: COBLAnCE: a French prospective cohort to study prognostic and predictive factors in bladder cancer and to generate real-world data on treatment patterns, resource use and quality of life - Simone Benhamou; Julia Bonastre; Bijan Ghaleh; Hélène Blanché; Pascal Eschwege; Arnauld Villers; Arnaud Méjean; François Radvanyi; Xavier Rébillard; Yves Allory; Thierry Lebret; Aldéric Fraslin; et al. (BMJ Open, 2023)
Purpose Bladder cancer is a complex disease with a wide range of outcomes. Clinicopathological factors only partially explain the variability between patients in prognosis and treatment response. There is a need for large cohorts collecting extensive data and biological samples to: (1) investigate gene-environment interactions, pathological/molecular classification and biomarker discovery; and (2) describe treatment patterns, outcomes, resource use and quality of life in a real-world setting.Participants COBLAnCE (COhort to study BLAdder CancEr) is a French national prospective cohort of patients with bladder cancer recruited between 2012 and 2018 and followed for 6 years. Data on patient and tumour characteristics, treatments, outcomes and biological samples are collected at enrolment and during the follow-up.Findings to date We describe the cohort at enrolment according to baseline surgery and tumour type. In total, 1800 patients were included: 1114 patients with non-muscle-invasive bladder cancer (NMIBC) and 76 patients with muscle-invasive bladder cancer (MIBC) had transurethral resection of a bladder tumour without cystectomy, and 610 patients with NMIBC or MIBC underwent cystectomy. Most patients had a solitary lesion (56.3%) without basement membrane invasion (71.7% of Ta and/or Tis). Half of the patients with cystectomy were stage ≤T2 and 60% had non-continent diversion. Surgery included local (n=298) or super-extended lymph node dissections (n=11) and prostate removal (n=492). Among women, 16.5% underwent cystectomy and 81.4% anterior pelvectomy.Future plans COBLAnCE will be used for long-term studies of bladder cancer with focus on clinicopathological factors and molecular markers. It will lead to a much-needed improvement in the understanding of the disease. The cohort provides valuable real-world data, enabling researchers to study various research questions, assess routine medical practices and guide medical decision-making.